Indocyanine-Green for Fluorescence-Guided Surgery of Brain Tumors: Evidence, Techniques, and Practical Experience - Cho, Steve S.; Salinas, Ryan; Lee, John Y. K. (Frontiers in Surgery, 2019)
The primary treatment for brain tumors often involves surgical resection for diagnosis, relief of mass effect, and prolonged survival. In neurosurgery, it is of utmost importance to achieve maximal safe resection while minimizing iatrogenic neurologic deficit. Thus, neurosurgeons often rely on extra tools in the operating room, such as neuronavigation, intraoperative magnetic resonance imaging, and/or intraoperative rapid pathology. However, these tools can be expensive, not readily available, time-consuming, and/or inaccurate. Recently, fluorescence-guided surgery has emerged as a cost-effective method to accurately visualize neoplastic areas in real-time to guide resection. Currently, 5-aminolevulinic-acid (5-ALA) remains the only fluorophore that has been approved specifically for fluorescence-guided tumor resection. Its use has demonstrated improved resection rates and prolonged progression-free survival. However, protoporphyrin-IX, the metabolic product of 5-ALA that accumulates in neoplastic cells, fluoresces in the visible-light range, which suffers from limited tissue penetration and significant auto-fluorescence. Near-infrared fluorescence, on the other hand, overcomes these problems with ease. Since 2012, researchers at our institution have developed a novel technique using indocyanine-green, which is a well-known near-infrared fluorophore used traditionally for angiography. This Second-Window-ICG (SWIG) technique takes advantage of the increased endothelial permeability in peritumoral tissue, which allows indocyanine-green to accumulate in these areas for intraoperative visualization of the tumor. SWIG has demonstrated utility in gliomas, meningiomas, metastases, pituitary adenomas, chordomas, and craniopharyngiomas. The main benefits of SWIG stem from its highly sensitive detection of neoplastic tissue in a wide variety of intracranial pathologies in real-time, which can help neurosurgeons both during surgical resections and in stereotactic biopsies. In this review of this novel technique, we summarize the development and mechanism of action of SWIG, provide evidence for its benefits, and discuss its limitations. Finally, for those interested in near-infrared fluorescence-guided surgery, we provide suggestions for maximizing the benefits while minimizing the limitations of SWIG based on our own experience thus far.